Critical Analysis of The Intersections Between Nursing and Midwifery - Altohefan, Zakia Mubarak Said; Mashni, Sohylah Abdullah Hefzullah Al; Alyami, Amal Nasser Salih; Demshiq, Bedoor saeed Dafer Al; Mahbub, Smar Mushbab Hadi Al; Altohefan, Khlood Mubarak Said; Alnusb, Rawan Yahia Abdulah; Algflah, Noora Hussein Mohd; Alhalali, Nada Saleh; Al abbas, Yahya Mohammed (Journal of Ecohumanism, 2024)
Nursing and midwifery are two health professions related to the scope of practice. However, they differ, especially in women’s and children’s health services. It recently became important to address overlaps between these fields, particularly about collaborative care models. To this end, this paper aims to investigate the complex role, shared tasks and dynamics, and issues relating to nurses and midwives in today’s society. It explores the role of the professions in patient care, defines the areas of convergence and drawbacks of these professions, and analyzes the effect of these professions on patient care. Some issues include role confusion, variation in professional training, and constraints of the overall health system, which are outlined in addition to the suggested approaches to enhance relations between nursing and midwifery.